Prosecution of genocide at international and national courts: a comparative analysis of approaches by ICTY/ICTR and Ethiopia/Rwanda - Onoria, Henry (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2003.